The Role of Education Level on Employee Performance - Milang, Ichsan; Firmansyah, Andrie; Sibay, Yusnita Fitarini (Yayasan Pendidikan Belajar Berdikari, 2024)
One of the company's human resources is its workforce. An key factor in accomplishing corporate objectives is employee performance in the organisation. Workers must be genuinely skilled in their professions and capable of providing the best possible service. An individual's ability to perform well can be impacted by their work environment, education, and training. This study is to examine the impact of education level on worker performance at PT. Fortune Maju Abadia, a business engaged in logistics and warehousing of goods. The population of this study consists of all 87 employees of PT. Fortune Maju Abadi in Makassar City, South Sulawesi. Using the Sloving approach, 75 respondents were included in the sampling. The validity test, reliability test, multiple linear analysis, coefficient of determination, classical assumption test, and hypothesis test are the data analytic techniques employed in this study.